Decolonising mathematics education: Towards a culturally relevant pedagogy - Babawande Emmanuel Olawale (Interdisciplinary Journal of Education Research)
This study investigates the existence of Eurocentric biases in mathematics teacher education programmes within South African higher education, focusing on the experiences and viewpoints of mathematics lecturers, mathematics student teachers, and department heads. It seeks to fill gaps in understanding how these biases impact educational practices and how the incorporation of culturally responsive pedagogy can eliminate them. Underpinned by an interpretivist paradigm, this study employed a qualitative research approach and a case study design. A purposive sampling technique was used to select two mathematics lecturers, ten mathematics student teachers in their fourth year of study, and a head of department, resulting in a total of thirty-nine samples from three purposively selected traditional universities across two provinces in South Africa. Thematic analysis was used to examine data gathered from semi-structured interviews, observational notes, and documents. Thematic coding was performed inductively, leading to the identification of principal themes that represent participants’ perspectives. Findings reveal a significant recognition of Eurocentric biases in mathematics education, with participants expressing concerns about the lack of culturally relevant content and pedagogical approaches. Based on the findings, the study concludes that addressing these biases is crucial for fostering inclusive educational environments and enhancing the effectiveness of culturally responsive teaching in mathematics. It underscores the need for mathematics teacher education programmes to align their curricula with the diverse cultural contexts of South Africa, promoting social justice and equity in mathematics education.